A stop-codon of the phosphodiesterase 11A gene is associated with elevated blood pressure and measures of obesity. Issue 3 (March 2016) - Ohlsson, Therese; Lindgren, Arne; Engström, Gunnar; Jern, Christina; Melander, Olle
Abstract : Objective: To identify stop-codon variants associated with blood pressure (BP). Methods: Illumina exome chip was genotyped in 5453 individuals of the population-based Malmö Diet and Cancer Study. We compared BP levels between carriers and noncarriers of all stop-codon variants found in at least 10 individuals and characterized these further based on literature evidence of functionality. Next, the association to ischemic stroke was evaluated in 2278 cases of ischemic stroke and 5969 controls. Results: We identified 19 stop-codon variants with nominally significant BP associations ( P < 0.05). One of these, located in the phosphodiesterase 11A ( PDE11A ) gene (R307X), has previously been reported to cause loss of PDE11A function and Cushing's syndrome in female carriers. In the Malmö Diet and Cancer Study, 1% of the population carried R307X and had age and sex-adjusted (mean, 95% confidence interval) 5.0, 0.29–9.7 ( P = 0.038), and 3.3, 0.83–5.7 ( P = 0.009) mmHg higher SBP and DBP than noncarriers and also significantly higher waist circumference and BMI. Among females, carriers of the R307X had age adjusted 8.3, 2.3–14 ( P = 0.006) and 4.7, 1.7–7.7 ( P = 0.002) mmHg higher SBP and DBP, 4.3, 0.84–7.8 ( P = 0.015) cm higher waist circumference and 1.7, 0.30–3.1 ( P = 0.018) kg/m 2 higher BMI. In addition, carriers of the R307X mutation had an odds ratio of ischemic stroke of 1.73 (95% confidence interval 1.06–2.82); P = 0.028. Conclusion: One percent of the Swedish population carries a PDE11A loss-of-function mutation associated with elevated BP, abdominal obesity, and risk of ischemic stroke.